Portfolio manager compensation and mutual fund performance - MA, Linlin (Institutional Knowledge at Singapore Management University, 2016)
We use a novel dataset to study the relation between individual portfolio manager compensation and mutual fund performance. Managers with explicit performance-based pay exhibit superior subsequent fund performance, especially when investment advisors link pay to performance over a longer time period. In contrast, alternative compensation arrangements, such as fixed salary, assets-based pay, or advisor-profits-based pay are not associated with superior performance. Our tests further show that the positive relation between performance-based contracts and fund performance is not driven by the selection of talented managers proxied by education background. Lastly, managers with performance-based pay engage less in risk-shifting activities.